Childhood trauma, parental bonding, and social cognition in patients with schizophrenia and healthy adults. Issue 1 (12th August 2020) - Rokita, Karolina I.; Dauvermann, Maria R.; Mothersill, David; Holleran, Laurena; Holland, Jessica; Costello, Laura; Cullen, Caroline; Kane, Ruán; McKernan, Declan; Morris, Derek W.; Kelly, John; Gill, Michael; et al.
Abstract: Objective: This study investigated associations between childhood trauma, parental bonding, and social cognition (i.e., Theory of Mind and emotion recognition) in patients with schizophrenia and healthy adults. Methods: Using cross‐sectional data, we examined the recollections of childhood trauma experiences and social cognitive abilities in 74 patients with schizophrenia and 116 healthy adults. Results: Patients had significantly higher scores compared with healthy participants on childhood trauma, and lower scores on parental bonding and social cognitive measures. Physical neglect was found to be the strongest predictor of emotion recognition impairments in both groups. Optimal parental bonding attenuated the impact of childhood trauma on emotion recognition. Conclusion: The present study provides evidence of an association between physical neglect and emotion recognition in patients with schizophrenia and healthy individuals and shows that both childhood trauma and parental bonding may influence social cognitive development. Psychosocial interventions should be developed to prevent and mitigate the long‐term effects of childhood adversities.